Anti-hypercholesterolemic Potency of Cassia Vera (Cinnamomum burmanni Nees ex Blume) Bark Extract - Fauzan Azima; D Muchtadi; F R Zakaria; B P Priosoeryanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
There has been limited report on the phytochemical content of cassia vera bark extract, and its potency as anti-hypercholesterolemic in rabbit is not known yet. The objectives of this research was to determine the phytochemical content and potency of anti-hypercholesterolemic of cassia vera bark extract using rabbit as the animal model.The research was devided into three stages, namely: (1) preparing cassia vera extraction with ethanol 96%; (2) analyzing phytochemical contents of cassia vera bark extract; (3) in vivo experiment, where twenty New Zealand White rabbits aged 5 months were used. Experimental rabbits were divided into 5 groups. The rabbits were fed with atherogenic cholesterol (0.1%) as positive control, RB11 standard feed as negative control, or cassia vera extracts (100 mg/kg/day or 200 mg/kg/day) or fenofibrat (15 mg/day) together with the atherogenic feed for 12 weeks. Levels of serum total cholesterol, triglyceride, HDL-cholesterol and LDL-cholesterol were determined at 0, 4, 8, and 12 week. At the end of the experiment formation of fatty liver were observed. The results showed that the ethanol extract of cassia vera bark contains total phenol (62.25%), flavonoids, triterpenoid, saponin and alkaloid. On the other hand, cassia vera bark extract was able to decrease total serum cholesterol from 443.3 mg/dl to 139.1 mg/dl, LDL cholesterol from 286.5 mg/dl to 95.8 mg/dl and triglyceride from 122.2 mg/dl to 61.2 mg/dl. Meanwhile, it increased HDL serum cholesterol from 29.1 mg/dl to 50.0 mg/dl in rabbit. It was also shown that the extract was able to decrease the everage fat globule on liver significantly from 27.47 globule to 3.59 globule per field view. Cassia vera bark extract with phytochemical content was found to be potential as anti-hypercholesterolemic and also in preventing fatty liver formatonr in rabbit. Key words :